CORRELATION OF QUALITY OF LIFE IN PATIENTS OF CIRRHOSIS OF LIVER WITH ETIOLOGY AND DISEASE SEVERITY USING DISEASE-SPECIFIC QUALITY OF LIFE QUESTIONNAIRE - Zuberi, Bader Faiyaz; Memon, Abdul Rauf; Afsar, Salahuddin; Qadeer, Rashid; Kumar, Rajesh (Journal of Ayub Medical College Abbottabad, 2007)
Background: Quality of Life has an important status in patient management suffering from chronic disease like cirrhosis and health related quality of life has significant impact on patient management. This study was conducted to evaluate the correlation of health related quality of life with disease severity in patients of cirrhosis of liver. Methods: This cross-sectional study was conducted at Medical Unit -IV, Dow University of Health Sciences, Karachi, during the period January 2006 to October 2006. All patients of cirrhosis of liver admitted during the study period were selected. Patients with encephalopathy, hepatocellular carcinoma were excluded. The 29 item chronic liver disease questionnaire (CLDQ) was administered to the patients by a postgraduate trainee. Internal validity of responses was checked statistically and correlation of responses was done with disease severity by Child-Pughs Criteria. Results: 109 patients were selected with 72 males and 37 females. Patient classification according to Child class A, B & C was 30, 38 & 41 respectively. The mean CLDQ score in the patients was 89.5 ±30.4. It correlated significantly with Child Class but did not correlate with the gender, age and etiology of cirrhosis. Conclusion: Health related CLDQ scores correlate with the severity of liver disease. Keywords: Cirrhosis; Chronic liver disease; Quality of life; Health quality of life.related